Associations between behavioural risk factors and overweight and obesity among adults in population-based samples from 31 countries. Issue 2 (March 2017) - Pengpid, Supa; Peltzer, Karl
Summary: Objective: Concern about overweight and obesity is growing worldwide, and more research to examine behaviours associated with the risk for increased weight in adult populations is needed. The aim of this study was to estimate associations between behavioural risk factors and overweight and obesity among adults in nationally representative population samples from 20 countries in Europe, 8 countries in Asia, Australia, Chile and USA. Methods: This secondary analysis is based on the International Social Survey Program (ISSP), 2011–2013, Health and Health Care Module. In a cross-sectional population-based survey (N = 48, 741) (mean age 46.6 years, SD = 17.4, age range 15–102 years) simple or multi-stage stratified random sampling was used, yielding representative samples of the adult population of respective countries. Body Mass Index was assessed by self-reported height and weight. Correlates were risk behaviours for chronic disease (smoking status, alcohol intake, consumption of fruits and vegetable (=FV), and physical activity). Results: Overall, for all 31 countries the prevalence of overweight or obesity was 44.1%, 31.7% overweight and 12.4% obese. In adjusted logistic regression models, among men and among women ex-smoking was positively associated with both overweight and obesity, while light or moderate smoking overall and among men were inversely related with obesity. Moderate alcohol use was positively associated with both overweight and obesity, while heavy alcohol use was negatively associated with overweight. The daily consumption of FV was found to be protective from both overweight and obesity, overall and for men but not for women. Physical activity was positively associated with overweight but not obesity. Conclusions: Some risk behaviours for chronic disease appear to be associated with overweight and obesity among adults. Interventions targeting these risk behaviours may have the potential to reduce weight.